IMPLEMENTASI KEBIJAKAN PEMERINTAH KOTA CIREBON DALAM MENINGKATKAN KETERTIBAN PEDAGANG KAKI LIMA (Studi Kasus di Jl. Siliwangi Kota Cirebon) - Winda Mirnawati; Heriyani Agustina; Hery Nariyah (Jurnal Ilmiah Publika, 2016)
ABSTRACT Street Vendors is a very complicated thing to ensure order. This became the basic tasks of municipal government in particular Cirebon Civil Service Police Unit to regulate street vendors, economic needs urgent that makes the street vendors sell on the road or on the sidewalk which should be forbidden by the local government area. The problem that arises if the implementation of policies regulating street vendors in the city of Cirebon can be increased in accordance with local regulations No. 9 of 2003 on Public Order policy on public order policy on public order by the local governments aimed so the vendors are supposed to walk not violate so as to create (Health, Beauty, and Order)The method used is qualitative research informant with the chairman of the peace and public order agencies Civil Service Police Unit Cirebon city and street vendors on the sidewalks and on the road in Jalan Siliwangi Cirebon City. Techniques of data collection using interviews, observation, data analysis, and data validity.Research results show that Control Policy Implementation street vendors in the city of Cirebon (status cases Jl. Siliwangi) is not optimal it is still a lot of problems including lack of regulatory policy on regulating local street vendors. Theories are taken using the theory of Van Meter and Van Horn include the size and purpose of the policy, resources, characteristics of the implementing agencies, communication between relevant organizations and implementing activities, social environment, political economy which is still unresolved due to the limited quality and quantity of the resources, the means, and infrastructure support order is not optimal.